2000
DOI: 10.1116/1.582363
|View full text |Cite
|
Sign up to set email alerts
|

Transfer etching of bilayer resists in oxygen-based plasmas

Abstract: Thin film imaging offers the possibility of extending 248 nm lithography to sub 150 nm resolution. We have been working on a 248 nm bilayer imaging scheme which utilizes a thin Si-containing resist on top of a thick, planarizing underlayer. The image is developed in the top layer and transferred to the underlayer via O 2 -based plasma etching. This article focuses on three aspects of the critical transfer etch process: etch resistance of the imaging resist, profile control and resist roughening. The imaging re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…During the etching process, phenomena such as polymer deposition, ion bombardment, rise in wafer temperature, selective etching of film components, and micromasking can either increase or decrease the LER of the feature. Mahorowala et al 23 sist to localized agglomeration and evaporation of components from the resist and plasma fluoropolymer deposition on top leading to microscopic variations in etch rate. They also explained that the different thermal expansion coefficients of the resist and fluoropolymer can cause ''wiggling'' of resist lines under certain etching conditions; for example, inadequate substrate cooling.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…During the etching process, phenomena such as polymer deposition, ion bombardment, rise in wafer temperature, selective etching of film components, and micromasking can either increase or decrease the LER of the feature. Mahorowala et al 23 sist to localized agglomeration and evaporation of components from the resist and plasma fluoropolymer deposition on top leading to microscopic variations in etch rate. They also explained that the different thermal expansion coefficients of the resist and fluoropolymer can cause ''wiggling'' of resist lines under certain etching conditions; for example, inadequate substrate cooling.…”
Section: Discussionmentioning
confidence: 98%
“…Past work demonstrated the effect of SO 2 -O 2 plasma etch chemistry on the SWR of 248 nm bilayer systems. 23 In this work, we evaluated a silicon-containing 193 nm bilayer system as an example of such a patterning strategy. The presence of silicon in the polymer resin boosts the etch resistance of the ultrathin top layer ͑ϳ130 nm͒, allowing for a thicker organic underlayer ͑ϳ360 nm͒ to be introduced.…”
Section: Nm Resistsmentioning
confidence: 99%
“…9k for the top view). It is observed that the LER profile (transferred through multiple etching processes) onto the substrate is not necessarily the same as the original LER profile onto the photoresist, Si-BARC, and hard mask [17,18,19,20,21,22]. Because the 2P2E technique uses multiple etching processes (e.g., from Si-BARC to hard mask, and from hard mask to silicon substrate), it is worthwhile to track the change in the LER profile.…”
Section: Impact Of Gate Ler On Performance Metricsmentioning
confidence: 99%
“…Although alignment is not an issue for biomolecule patterning based on polymer liftoff, [35] as it is an integrated process, this method involves extra steps of deposition and etching a polymer film, which increases the complexity of the process. Challenges are also encountered as the size of the photolithographic patterns decrease due to the increase in line-edge roughness (LER) [38,39] and the isotropic nature of oxygen plasma etch. [39] Patterned gold has been used for creating protein patterns using thiolbased linkers, [40] but gold surfaces cannot be tolerated in some biosensors [4][5][6]10] as gold interferes with the optical signal or conductivity of the sensor.…”
mentioning
confidence: 99%
“…Challenges are also encountered as the size of the photolithographic patterns decrease due to the increase in line-edge roughness (LER) [38,39] and the isotropic nature of oxygen plasma etch. [39] Patterned gold has been used for creating protein patterns using thiolbased linkers, [40] but gold surfaces cannot be tolerated in some biosensors [4][5][6]10] as gold interferes with the optical signal or conductivity of the sensor. This technique also includes extra photolithographic and lift-off processing steps for patterning gold.…”
mentioning
confidence: 99%